Microbes, bioactive compounds, quality characteristics, and structural changes during the storage of Qingke barley fresh noodles. Issue 12 (3rd November 2019) - Tuersuntuoheti, Tuohetisayipu; Wang, Zhenhua; Wang, Ziyuan; Duan, Mengjie; Zheng, Yanyan; Wu, Yan; Liang, Shan; Li, Xinping; Zhang, Min
Abstract: Changes of microbes, bioactive compounds, protein structures, and noodle qualities in Qingke barley (one of the Tibetan barleys) fresh noodles (QBFN) stored at 25°C were evaluated. The results showed that an increase in total plate count (TPC) and total mold count (TMC) occurred after 12 hr, and Pantoea, Erwinia, Bacillus for the bacteria, Penicillium and Aspergillus for the mold became dominant spoilage microorganisms at the end of storage.In addition, according to the microbial growth at 25°C, the microbial growth models were built for both TPC and TMC, and the microbial growth models were well fitted by logistic model, with higher fitting precision. The fitting equations were Y = 3.7642–3.7/[1+( t /26.597) 3.1 ], R 2 = 0.9942 and Y = 1.7553–1.7546/[1+( t /19.8) 3.4 ], R 2 = 0.9999. Due to the polyphenol oxidization (PPO), the total phenol and flavonoid contents decreased from 77 and 36 mg/100 g to 49 and 18 mg/100 g, respectively. The pH value, color, textural properties, and cooking quality decreased significantly ( p < .05). The disulfide (SS) bond content decreased from 2.9 to 1.6 µmol/g, while the free sulfydryl (SH) content increased from 0.9 to 1.3 µmol/g; the cost of a significant reduction in α‐helix induced an increase in the random coil with the deterioration of QBFN. The relative abundance of strong bounded water decreased while the relative abundance of weakly bounded water and free water increased, which indicated the destruction of the structure of protein encapsulating starch in QBFN. Moreover, Pearson correlation analysis showed that changes of TPC, TMC, SS/SH bond content, and water state were also significantly correlated with the appearance, textural properties, and cooking quality of QBFN. Practical applications: Investigating changes in microbe diversity, bioactive compound, protein structure, water state, and noodle quality during storage at 25 ± 1°C will help us understand the mechanisms and dynamics of QBFN deterioration. Identification of the dominant microbes that contribute to noodle spoilage and the changes of bioactive compounds help us determine suitable methods to inhibit the growth of microbes and to prevent the loss of bioactive compounds. Moreover, correlation analysis may help us understand the relationship between noodle quality and microbe, water state, and protein structure, and provide a theoretical basis for improving noodle quality.